Pinpointing nitrogen oxide emissions from space - Beirle, Steffen; Wagner, Thomas (Science advances, 2019)
Satellite observations of nitrogen dioxide (NO2) provide valuable information on the location and strength of NOx emissions, but spatial resolution is limited by horizontal transport and smearing of temporal averages due to changing wind fields. In this study, we map NOx emissions on high spatial resolution from TROPOMI observations of NO2 combined with wind fields based on the continuity equation. The divergence of horizontal fluxes proves to be highly sensitive for point sources like exhaust stacks. Thus, NOx emissions from individual power plants can be resolved and quantified even on top of considerably high urban pollution from the Saudi Arabian capital city Riyadh. This allows us to catalog NOx emissions from large point sources globally, as demonstrated for South Africa and Germany, with a detection limit of about 0.11 kg/s down to 0.03 kg/s for ideal conditions. - Power plant exhausts can be identified and quantified from satellite observations. - Power plant exhausts can be identified and quantified from satellite observations.
Gesehen am 14.01.2020